1984
DOI: 10.1152/ajpregu.1984.247.1.r114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron-deficiency anemia on hormone levels and thermoregulation during cold exposure

Abstract: When exposed to an ambient temperature of 4 degrees C, iron-deficient anemic rats become hypothermic. This lesion is related more to anemia than to tissue iron deficiency, since exchange transfusion to hematocrits over 25 restored normal thermoregulatory performance. Likewise poor cold responses were induced in control rats by transfusion to low hematocrits. Cold sensitivity in all anemic animals was paralleled by poor thyroid responses: there was a significant positive correlation between hematocrit and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 0 publications
4
39
1
1
Order By: Relevance
“…The present study explored the hypothesis that iron deficiency might impair thyroid metabolism, as previously reported in animal and human studies (Dallman et al, 1978, 1980; Chen et al, 1983;Beard et al, 1984Beard et al, , 1990aMartinez-Torres et al, 1984;Brigham and Beard, 1995). Our findings confirm that an improvement in iron status had a positive impact on serum concentrations of thyroid hormones in iron-deficient adolescent girls.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study explored the hypothesis that iron deficiency might impair thyroid metabolism, as previously reported in animal and human studies (Dallman et al, 1978, 1980; Chen et al, 1983;Beard et al, 1984Beard et al, , 1990aMartinez-Torres et al, 1984;Brigham and Beard, 1995). Our findings confirm that an improvement in iron status had a positive impact on serum concentrations of thyroid hormones in iron-deficient adolescent girls.…”
Section: Discussionsupporting
confidence: 87%
“…Theoretically, severe iron deficiency could lower thyroperoxidase activity and interfere with thyroid hormone synthesis. Animal studies have documented that weanling rats fed iron-deficient diets have significantly lower T3 and T4 compared to rats fed adequate iron (Chen et al, 1983;Beard et al, 1984;Brigham and Beard, 1995). Recently Hess and co-workers (2002) showed that thyroid peroxidase activity is significantly reduced in iron deficiency anaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies carried out in rats have indicated that iron, T4 and T3 levels in circulation were significantly decreased during conversion of thyroxine (T4) to triiyodotironin (T3). [4][5][6][7] However, effects of iron deficiency anemia on thyroid function-related studies are mostly based on animal studies and results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…These include impaired work performance (Cook et al, 1994;Lozoff et al, 1998), behaviour and intellectual performance (Moffatt et al, 1994). In addition, impaired thermoregulatory mechanisms (Beard et al, 1984) and an increased risk of infection (Dallman, 1987) have been documented in iron de®ciency status. Iron de®ciency has also been found to be associated with adverse pregnancy outcomes (Yip & Dallman, 1996).…”
Section: Introductionmentioning
confidence: 99%